Substance P spinal signaling induces glial activation and nociceptive sensitization after fracture. (3rd December 2015) - Li, W.-W.; Guo, T.-Z.; Shi, X.; Sun, Y.; Wei, T.; Clark, D.J.; Kingery, W.S.
Highlights: Substance P signaling contributed to spinal glial activation and nociceptive sensitization. C-fiber afferent signaling induced spinal glial activation and hypersensitivity. Neuroglial activation contributed to the maintenance of chronic post fracture hypersensitivity. Abstract: Tibia fracture in rodents induces substance P (SP)-dependent keratinocyte activation and inflammatory changes in the hindlimb, similar to those seen in complex regional pain syndrome (CRPS). In animal pain models spinal glial cell activation results in nociceptive sensitization. This study tested the hypothesis that limb fracture triggers afferent C-fiber SP release in the dorsal horn, resulting in chronic glial activation and central sensitization. At 4 weeks after tibia fracture and casting in rats, the cast was removed and hind paw allodynia, unweighting, warmth, and edema were measured, then the antinociceptive effects of microglia (minocycline) or astrocyte (L-2-aminoadipic acid (LAA)) inhibitors or an SP receptor antagonist (LY303870) were tested. Immunohistochemistry and PCR were used to evaluate microglial and astrocyte activation in the dorsal horn. Similar experiments were performed in intact rats after brief sciatic nerve electric stimulation at C-fiber intensity. Microglia and astrocytes were chronically activated at 4 weeks after fracture and contributed to the maintenance of hind paw allodynia and unweighting. Furthermore, LY303870 treatment initiated at 4 weeks after fracture partially reversed both spinal glial activation and nociceptive sensitization. Similarly, persistent spinal microglial activation and hind paw nociceptive sensitization were observed at 48 h after sciatic nerve C-fiber stimulation and this effect was inhibited by treatment with minocycline, LAA, or LY303870. These data support the hypothesis that C-fiber afferent SP signaling chronically supports spinal neuroglial activation after limb fracture and that glial activation contributes to the maintenance of central nociceptive sensitization in CRPS. Treatments inhibiting glial activation and spinal inflammation may be therapeutic for CRPS.